Fatores envolvidos nos comportamentos de omissão circunstancial e de recusa do uso do preservativo em homens que fazem sexo com homens - Garcia, Roberto (2016)
This study aimed to identify and understand factors involved in conducts of circumstantial omission and refusal of condom use with casual and/or stable partners by MSM living with HIV+; and as a specific objective, to understand the behavior of intentional and deliberate refusal of condom use among MSM with HIV+. In this research of mixed methods, comparing reports between quantitative and qualitative components, 178 participants were selected for the quantitative stage (total sample = T), who filled out a sociodemographic form with condom usage habits, as well as two scales – Barratt Impulsiveness Scale (BIS-11) and Sexual Compulsivity Scale (SCS). From this universe, 81 participants were selected for the qualitative stage (Subsample = S-2), also answering to three fictional-projective stories and rating a 2014 National Campaign Poster on HIV. For the qualitative analysis we used the Discourse of the Collective Subject; and for the quantitative analysis we opted for the combination of Natural Language Processing and triangulation with qualitative results. Among the main findings we highlight that, in the quantitative stage, from the 73 subjects (41%) (T) that had declared the use of condom in all their sexual relations, only 14 (17.3%) (S-2) effectively admitted its use in the qualitative stage, indicating divergence between the two groups. Similarly, this contradiction was repeated as to the use of psychoactive substances – characterized in this study as the main triggering factor of condom use omission –, since only 28% (T) initially admitted having used them, in contrast to the total of 56% (S- 2) in the qualitative stage. Another difference that would mean a "clear proof" of failure and refusal of condom use occurred in their assertion of having contracted STIs after the HIV diagnosis, identified in 35.5% (T) and 52% (S-2), respectively. Another finding was the intentional and deliberate refusal of condom use associated with signs of compulsive sexual behavior and risk in pleasure, including the barebackers and those practiced in cruising areas. Given the significant divergences between the initial reports of the participants and what was later identified in the two stages of this research, we conclude that clinical guidelines and public policies should be cautious in research interpretation, with proper checkings associated with further investigations. The clinical features observed in this study, including the evidence of impulsive and compulsive sexual behaviors, may constitute determining benchmarks to be taking into account in future actions associated to the use of condoms by MSM with HIV+